Building agroecological traction: Engaging discourse, the imaginary, and critical praxis for food system transformation - Kelinsky-Jones, Lia R.; Niewolny, Kim L.; Stephenson, Max O. (Frontiers in Sustainable Food Systems, 2023)
Shifting the current food system toward a more sustainable and equitable model requires an alternative imaginary. Agroecology represents such an approach, but despite the construct’s promise, policy and academic communities alike continue to maintain the current system. We contend that shifting away from the existing, dominant food system requires researchers to engage stakeholders with discourses that give meaning to an agroecological imaginary. We provide a methodological case study for how interested analysts may build agroecological traction through critical praxis. We advance our argument theoretically, methodologically, and empirically. Theoretically, we draw on scholarship arguing that food system transformation requires a discursive imaginary. Methodologically, we outline how Critical Discourse Analysis (CDA) as both a theoretical and methodological framework, illuminates the discursive power that shapes the future of food. We first used CDA to analyze United States Agency for International Development (USAID) policy, and subsequently presented those results to focus groups comprised of USAID-funded university-based research-practitioners. Empirically, we suggest that our methodology represents one possible mechanism or strategy to encourage the dialogue necessary to secure a new critical food system praxis. We conclude by offering recommendations for future inquiry.